Complex inner and outer setting interactions determine feasibility and readiness of developing primary care registries in small island developing states: sequential mixed methods study - Sobers, Natasha P.; Agard, Joeleita; Campbell, Jacqueline; Lewis, Kia; Jeyaseelan, S. M. (Frontiers in Health Services, 2025)
IntroductionWe assessed feasibility and readiness for registry development and sought to understand the factors likely to affect the implementation of a registry into health systems in small island developing states (SIDS).MethodsWe conducted online quantitative surveys and focus groups among health managers in four SIDS. Both survey and focus group guides were developed primarily based on four domains (inner setting, outer setting, individual characteristics and implementation process) of the Consolidated Framework for Implementation Research (CFIR). Focus groups within each of four territories were recorded, transcribed verbatim and analyzed using thematic content analysis using a deductively derived coding framework. We synthesized our findings using a systems archetype informed by the common themes emerging from the dual methods.FindingsFrom the 37 respondents of the online survey, 40% and 16% identified diabetes and hypertension as the highest priority NCDs for registry development. Respondents were more concerned about monitoring and improving care for patients (65%) than about determining disease burden (16%) or outcomes monitoring (8%). Strong mission alignment, external pressure and support and emerging data protection laws were identified as potential facilitators. Participants reported lack of human resource capacity and funding to support NCD registry and poor information systems infrastructure. The emerging systems archetype indicated that lack of investment in human and systems infrastructure were significant threats to registry success.DiscussionDespite external interest in registry development, infrastructural and human resource capacity barriers are likely contribute to a sub-optimal implementation in SIDS. We recommend greater collaboration between countries and enhanced regional support to overcome the challenges.